The Influence Of Product Quality And Price Perception On Interest In Buying Realme Smartphones At Cahaya Cell Argamakmur - Lesti Handayani; Islamuddin (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
The aim of the research is to determine the influence of product quality and price perception on Smartphone Realme consumer buying interest at Cahaya Cell Argamakmur. And to find out which factors most dominantly influence consumer buying interest. This research used quantitative methods on 160 respondents. The population used in this research were consumers at Cahaya Cell Argamakmur and sampling in this research was a non-probability sampling technique. Based on the results of multiple linear regression, the regression equation Y = 5.347 + 0.225 (X1) + 0.261(X2) is obtained. The research results and hypothesis show that product quality and price perception have a partial or simultaneous positive effect on consumer purchase interest